RETRACTED: Educational coworking as a means of developing sustainable mobility of students - Shefer Olga; Belousov Alexander; Kraineva Svetlana; Lebedeva Tatyana; Erentraut Elena; Akhkamova Yulia; Kochetkova Galina; Yunusova Svetlana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001